Evaluating Islamic Religious Education Programs in Rural Elementary Schools: A CIPP Model Analysis - Jumroh; Ahmad Yani; Budi Manfaat (Journal of Contemporary Islamic Education, 2026)
This study aims to evaluate the Islamic Religious Education (PAI) program at UPTD SDN 4 Temiyang, Indramayu, using the CIPP evaluation model. This research employed a qualitative evaluative approach through interviews, observations, and document analysis involving the school principal, Islamic education teacher, classroom teachers, students, and parents. The findings show that the PAI program is supported by a strong religious school culture, formal curriculum documents, and consistent religious habituation activities. However, the effectiveness of the program is constrained by a systemic integration gap among context, input, process, and product dimensions. Contextually, students’ religious behavior is influenced by unequal reinforcement between school and home environments. In the input dimension, curriculum documents, teachers, and basic facilities are available, but their use in active, contextual, and media-supported learning remains limited. In the process dimension, religious habituation effectively strengthens discipline, worship routines, and moral conduct, while classroom instruction is still dominated by conventional methods. This creates a tension between behaviorist habit formation and constructivist meaning making. In the product dimension, outcomes are more visible in students’ religious behavior and worship practices than in deep conceptual understanding and independently internalized values. From the perspective of Islamic education, the program has attempted to integrate ta’lim, tarbiyah, and ta’dib, but these dimensions have not yet functioned as a coherent system. This study concludes that improving PAI program effectiveness requires stronger integration among school culture, classroom pedagogy, family involvement, and comprehensive assessment of cognitive, affective, and psychomotor outcomes.